2005
DOI: 10.1083/jcb.200410006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal separation of replication and recombination requires the intra-S checkpoint

Abstract: In response to DNA damage and replication pausing, eukaryotes activate checkpoint pathways that prevent genomic instability by coordinating cell cycle progression with DNA repair. The intra-S-phase checkpoint has been proposed to protect stalled replication forks from pathological rearrangements that could result from unscheduled recombination. On the other hand, recombination may be needed to cope with either stalled forks or double-strand breaks resulting from hydroxyurea treatment. We have exploited fission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
102
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 40 publications
(55 reference statements)
16
102
0
3
Order By: Relevance
“…Uncoupling the interaction between Cds1 and Mus81-Eme1 results in the unscheduled presence of Mus81-Eme1 on chromatin during replication arrest and the subsequent initiation of recombinogenic processes (5). Apparent negative regulation of recombination repair proteins by the replication checkpoint is consistent with the failure to observe recombination repair foci in wild-type fission yeast during hydroxyurea-induced replication arrest (6). Notably, recombination repair foci are observed following release from replication arrest and entry into G 2 phase or during the arrest if Cds1 is deleted (6).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Uncoupling the interaction between Cds1 and Mus81-Eme1 results in the unscheduled presence of Mus81-Eme1 on chromatin during replication arrest and the subsequent initiation of recombinogenic processes (5). Apparent negative regulation of recombination repair proteins by the replication checkpoint is consistent with the failure to observe recombination repair foci in wild-type fission yeast during hydroxyurea-induced replication arrest (6). Notably, recombination repair foci are observed following release from replication arrest and entry into G 2 phase or during the arrest if Cds1 is deleted (6).…”
supporting
confidence: 58%
“…Apparent negative regulation of recombination repair proteins by the replication checkpoint is consistent with the failure to observe recombination repair foci in wild-type fission yeast during hydroxyurea-induced replication arrest (6). Notably, recombination repair foci are observed following release from replication arrest and entry into G 2 phase or during the arrest if Cds1 is deleted (6).…”
mentioning
confidence: 51%
“…To determine whether this reflects active damage, we employed a YFP-tagged Rad22 (ScRad52) to visualize repair foci (Lisby et al 2001(Lisby et al , 2003(Lisby et al , 2004Du et al 2003;Meister et al 2003Meister et al , 2005. We observed that 67.3% of hsk1-1312 cells and 61.6% of Dswi1 cells growing asynchronously at 25°had at least one Rad22YFP focus, vs. only 8.5% of wild-type cells (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Our data showing an interaction both genetically and physically with Rad22 suggested that Mst1 may contribute to repair of DSBs by influencing homologous recombination. Rad22 has also been implicated in recovery from HU (Meister et al 2005;Bailis et al 2008). Therefore, we examined mst1-L344S mutants for evidence of a role in the damage response.…”
Section: Resultsmentioning
confidence: 99%